P37 The assessment of the cardioprotective properties of metformin during sunitinib-induced cytotoxicity. (21st March 2018) - Kuburas, Refik; Gharanei, Mayel; Haussmann, Irmgard; Maddock, Helen; Sandhu, Hardip
Abstract : Multi-tyrosine kinase inhibitor Sunitinib is associated with cardiotoxicity, in contrast the anti-type-2 diabetic Metformin is associated with cardioprotective properties via adenosine monophosphate-activated protein kinase (AMPK) activation. We investigated whether treatment of rat langendorff hearts with Metformin attenuated Sunitinib-induced cytotoxicity via AMPK. We further investigated the cotreatment of Metformin with Sunitinib using HepG2 and HL60 cancer cell lines to reveal if potential adjunctive therapy drugs interfere with and prevent the anti-cancer activity of chemotherapy agents. Male Sprague-Dawley rat hearts were Langendorff perfused with vehicle or, Sunitinib (1 µM) in the absence or presence ±Metformin (50 µM)±S-4-Nitro-benzyl-theonosine (AMPK inhibitor, NBTI) (1 µM) for 155 min. Functional parameters were measured throughout the experiment (n=6), heart tissue was also assessed for necrosis or relevant protein phosphorylation (n=6). HepG2 and HL60 cells treated in the presence of Sunitinib (0.1–100 µM)±Metformin (50/1000 µM)±NBTI (1 µM) (n=6) were assessed for cell viability.. Sunitinib caused a significant increase in myocardial infarcted tissue (Vehicle=11%±1% vs Sunitinib=31±2%, p<0.05). Metformin co-administration restored viable myocardial tissue (Sunitinib+Metformin=20%±2%, p<0.05), NBTI attenuated Metformin's cardioprotection (Sunitinib+Metformin+NBTI=30%±2%, p<0.05). Sunitinib decreased cell viability in HepG2 and HL60 cells at doses 5–100 µM (HepG2 IC50=21 µM, HL60 IC50=10 µM). Cytotoxicity of Sunitinib was maintained in presence of 0.05 mM Metformin (HepG2 IC50=76 µM, HL60 IC50=22 µM) and 1 mM Metformin (HepG2 IC50=44 µM, HL60 IC50=24 µM). Metformin (30–1000 µM) did not reduce HepG2 and HL60 cell viability. This study shows for the first time that Metformin protects the hearts against Sunitinib-induced cardiotoxicity via AMPK activation which was attenuated with NBTI.